A network of noise: designing with a decade of data to sonify JANET - Emsley, I; De Roure, D; Chamberlain, A (Association for Computing Machinery, 2017)
The existing sonification of networks mainly focuses on security. Our novel approach is framed by the ways in which network traffic changes over the national JANET network. Using a variety of sonification techniques, we examine the user context, how this sonification leads to system design considerations, and feeds back into the user experience.